For better or for worse? A pre–post exploration of the impact of the COVID‐19 lockdown on cannabis users. - Cousijn, Janna; Kuhns, Lauren; Larsen, Helle; Kroon, Emese (Addiction, 2021)
Background and aims: Lockdown measures aimed at limiting the number of infections and deaths from the coronavirus disease 2019 (COVID‐19) have introduced substantial psychosocial stressors in everyday life. We aimed to investigate the influence of the Dutch lockdown on cannabis use and cannabis use disorder (CUD) and investigate relations with change in mental wellbeing and experienced psychosocial stressors during the lockdown. Design Explorative longitudinal baseline‐, pre‐ and during lockdown survey study. Setting: The Netherlands, on‐line between January 2019 and May 2020. Participants: Community sample of 120 monthly to daily cannabis users and reference group of 63 non‐using controls. Measurements Change in cannabis use and CUD symptom severity from baseline to pre‐ to post‐lockdown. Change in cannabis use motives, mental health, quality of social relationships and job status from pre‐ to post‐lockdown. Findings In cannabis users, lockdown related to increased cannabis use [B = 1.96, 95% confidence interval (CI) = 0.26–3.66, P = 0.024], but not CUD symptom severity. Cannabis users experienced 30% job loss and increased loneliness [P < 0.001, Bayes factor (BF)10 > 100], while contact with partners (P = 0.005, BF10= 8.21) and families improved (P < 0.001, BF10 = 19.73), with no differences between cannabis users and control. Generally, mental health problems (all Ps > 0.277, all BF10 < 0.139) did not change, but individual differences were significant and severity of cannabis use pre‐lockdown, COVID‐19‐related worries, change in anxiety, expansion motives, social motives and family contact all uniquely related to variance in change in cannabis use or CUD. Conclusions: While cannabis use among daily cannabis users in the Netherlands increased at the group level during the period of COVID‐19 lockdown, the effect of the first months of lockdown on cannabis use disorder severity and mental wellbeing varied significantly among individual daily cannabis users.